Makna Simbolik Tari Podang dalam Masyarakat Nagari Koto Nan Gadang Kota Payakumbuh Provinsi Sumatera Barat - Siti Rosana; Auliana Mukhti i Maghfirah; Ninon Syofia; Zulfikar Rizki Ananda (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research discusses the symbolic meaning of Podang Dance in the community of Nagari Koto Nan Gadang, Payakumbuh City. Podang Dance is a traditional art originaly from Minangkabau martial arts practices and has developed as part of the local cultural heritage. This study aims to describe and analyze the symbolic meanings contained in the performance elements of Podang Dance, including movement, music costume,and property. This research employed a qualitative method with a descriptive analytical approach. Data were collected through observation, interviews, and documentation. The data were analyzed using Roland Barthes’ semiotic theory, which focuses on denotative and connotative meanings to reveal the cultural symbols contained in the Podang Dance performance. The results of the study indicate that Podang Dance functions not only as entertainment, but also contains cultural values, moral values, and character education within the community of Nagari Koto Nan Gadang. Each movement in the dance represents agility, bravery, self-control, and mutual respect. The podang property symbolizes vigilance and heroism, while the costumes and musical accompaniment strengthen the Minangkabau cultural identity. Therefore, Podang Dance plays an important role as a medium for cultural preservation and the transmission of traditional values to the younger generation.